2014
DOI: 10.1097/01.tp.0000437430.89485.a0
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Platelet Migration in the Postischemic Liver by Blocking Protease-Activated Receptor 4

Abstract: Our in vivo data suggest PAR-4 as a potential target for future therapeutic strategies against platelet-mediated liver injury on transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…Platelets have been implicated in worsening ischaemia-reperfusion injury, which accounts for 10% of early graft dysfunction and predisposes to acute and chronic rejection. The suggested mechanism is via platelet sequestration in the hepatic microvasculature, where up regulation of proinflammatory endothelial injury and necrotic apoptosis could be exacerbated by platelet transfusion [22] . The vasoactive effects of platelets may cause other negative systemic consequences such as pulmonary hypertension and haemodynamic disturbance.…”
Section: Drivers For Transfusion-free Transplantationmentioning
confidence: 99%
“…Platelets have been implicated in worsening ischaemia-reperfusion injury, which accounts for 10% of early graft dysfunction and predisposes to acute and chronic rejection. The suggested mechanism is via platelet sequestration in the hepatic microvasculature, where up regulation of proinflammatory endothelial injury and necrotic apoptosis could be exacerbated by platelet transfusion [22] . The vasoactive effects of platelets may cause other negative systemic consequences such as pulmonary hypertension and haemodynamic disturbance.…”
Section: Drivers For Transfusion-free Transplantationmentioning
confidence: 99%
“…In addition, it has also been postulated that platelets are essential for the liver to regenerate properly following a partial liver resection (42). Platelet aggregation has been associated with microvascular perfusion defects, apoptotic cell death, vascular oxidative stress and an inflamed endothelium (43), all suggesting a pathophysiological connection between platelets and hepatocytes. In the present study, GalN induced OH • radicals in platelets; however, it did not cause platelet aggregation when analyzed alone or in collagen pretreated conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Coagulation inhibition takes multiple forms, uncovering the complexity of this pathway. As a first example, in a mouse model of liver IRI, the Protease activated receptor (PAR)-4 pathway was targeted [65], while a clinical study showed that PAR-1 is expressed by DCs in DGF grafts and its activation may induce complement production and a Th1 bias [66]. Secondly, in a mouse model of hepatic IRI, recombinant human thrombomoduling was protective, and specifically this activity was brought through the N-terminal lectin-like domain 1 (D1) subunit, involving TLR4 signaling [67].…”
Section: Additives In Preservation Solution: Improve the Now Whilementioning
confidence: 99%